Cyprus' diatom diversity and the association of environmental and anthropogenic influences for ecological assessment of rivers using DNA metabarcoding - Pissaridou, Panayiota; Vasselon, Valentin; Christou, Andreas; Chonova, Teofana; Papatheodoulou, Athina; Drakou, Katerina; Tziortzis, Iakovos; Dörflinger, Gerald; Rimet, Frederic; Bouchez, Agnès; Vasquez Christodoulou, Marlen (My University, 2021)
Human activities are the leading cause of environmental impairments. Appropriate biomonitoring of ecosystems is needed to assess these activities effectively. In freshwater ecosystems, periphytic and epilithic biofilms have diatom assemblages. These assemblages respond rapidly to environmental changes, making diatoms valuable bioindicators. For this reason, freshwater biomonitoring programs are currently using diatoms (e.g., Water Framework Directive). In the past ten years, DNA metabarcoding coupled with next-generation sequencing and bioinformatics represents a complementary approach for diatom biomonitoring. In this study, this approach is used for the first time in Cyprus by considering the association of environmental and anthropogenic pressures to diatom assemblages. Statistical analysis was then applied to identify the environmental (i.e., river types, geo-morphological) and anthropogenic (i.e., physicochemical, human land-use pressures) variables' role in the observed diatom diversity. Results indicate differences in diatom assemblages between intermittent and perennial rivers. Achnanthidium minutissimum was more abundant in intermittent rivers; whereas Amphora pediculus and Planothidium caputium in perennial ones. Additionally, we could demonstrate the correlation between nutrients (e.g., nitrogen, phosphorus), stations' local characteristics (e.g., elevation), and land use activities on the observed differences in diatom diversity. Finally, we conclude that multi-stressors and anthropogenic pressures together as multiple stressors have a significant statistical relationship to the observed diatom diversity and play a pivotal role in determining Cyprus' rivers' ecological status.
Keywords: DNA metabarcoding; Diatom; Ecological assessment; Intermittent; Multiple pressure; Perennial